2010
DOI: 10.1007/s10532-010-9350-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening for and isolation and identification of malathion-degrading bacteria: cloning and sequencing a gene that potentially encodes the malathion-degrading enzyme, carboxylestrase in soil bacteria

Abstract: Five malathion-degrading bacterial strains were enriched and isolated from soil samples collected from different agricultural sites in Cairo, Egypt. Malathion was used as a sole source of carbon (50 mg/l) to enumerate malathion degraders, which were designated as IS1, IS2, IS3, IS4, and IS5. They were identified, based on their morphological and biochemical characteristics, as Pseudomonas sp., Pseudomonas putida, Micrococcus lylae, Pseudomonas aureofaciens, and Acetobacter liquefaciens, respectively. IS1 and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 23 publications
(23 reference statements)
2
36
1
4
Order By: Relevance
“…However, several other studies have found little microbial degradation of chlorpyrifos. Goda et al (2010) showed that the intact cells of Pseudomonas putida IS168 were able to degrade fenitrothion, diazinon and profenofos when present as sole carbon sources, but failed to grow on chlorpyrifos. Trichloropyridinol (TCP), one of the main chlorpyrifos metabolites, has antimicrobial properties (Cáceres et al, 2007;Feng et al, 1997;Racke et al, 1990), possibly accounting for the scarcity of chlorpyrifos-degrading microorganisms.…”
Section: Micromial Degradationmentioning
confidence: 99%
“…However, several other studies have found little microbial degradation of chlorpyrifos. Goda et al (2010) showed that the intact cells of Pseudomonas putida IS168 were able to degrade fenitrothion, diazinon and profenofos when present as sole carbon sources, but failed to grow on chlorpyrifos. Trichloropyridinol (TCP), one of the main chlorpyrifos metabolites, has antimicrobial properties (Cáceres et al, 2007;Feng et al, 1997;Racke et al, 1990), possibly accounting for the scarcity of chlorpyrifos-degrading microorganisms.…”
Section: Micromial Degradationmentioning
confidence: 99%
“…Due to extensive use of malathion, exposure risk of living organisms including human beings is very high. Malathion degradation by microorganisms has been reported by several items (Goda et al, 2010;Singh et al, 2012;Janeczko et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There are different types of enzymes responsible for the degradation of OPCs, the most important of them are phosphotriesterases and carboxylesterases (Goda et al, 2010). Carboxylesterases are enzymes found in the α/β-hydrolase fold family that catalyze the hydrolysis of carboxyl esters via the addition of water (Hosokawa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the degradation of malathion by microbes (Xie et al, 2009;Goda et al, 2010;Singh et al, 2012) and most of these studies were carried out using pure cultures. Little information is available concerning degradation of malathion by activated sludge culture (Barik et al, 1984;Kanazawa, 1987 Evaluation of substrate inhibition becomes an important consideration in the treatment of toxic compounds in engineered systems such as activated sludge processes (Hao et al, 2002), and mathematical modeling can be helpful for understanding the behavior of biological processes and predicting the component concentrations in the system (Tziotzios et al, 2008).…”
Section: Introductionmentioning
confidence: 99%